Influence of the increase in intestinal permeability and microbiota change in the development of Hashimoto's thyroiditis - Systematic review - Desislav G. Tomov; Boryana A. Levterova; Valentina N. Mihailova; Dimitar M. Troev; Maria Z. Miteva; Yordanka I. Uzunova; Maria M. Orbetzova (Endocrine and Metabolic Science)
The etiology of Hashimoto's thyroiditis is still unclear. Genetic predisposition and the effects of various environmental factors are discussed. The present article is a systematic review of publications on the occurrence and development of this disease in the presence of impaired functions of the gastrointestinal tract and changes in the microbiota. Increased intestinal permeability, as well as changes in the microbiota, can disrupt the normal functioning of the immune system and can lead to the development of an autoimmune disease. Normalization of the diversity of the microbiota before an autoimmune process occurs can be achieved both with the use of pro-biotic strains and with appropriate dietary changes.